Breakfast consumption is positively associated with nutrient adequacy in Canadian children and adolescents. Issue 8 (8th September 2014) - Barr, Susan I.; DiFrancesco, Loretta; Fulgoni, Victor L.
Abstract : Although breakfast is associated with more favourable nutrient intake profiles in children, limited data exist on the impact of breakfast on nutrient adequacy and the potential risk of excessive intakes. Accordingly, we assessed differences in nutrient intake and adequacy among breakfast non-consumers, consumers of breakfasts with ready-to-eat cereal (RTEC) and consumers of other types of breakfasts. We used cross-sectional data from 12 281 children and adolescents aged 4–18 years who took part in the nationally representative Canadian Community Health Survey, 2004. Mean nutrient intakes (obtained using a multiple-pass 24 h recall method) were compared among the breakfast groups using covariate-adjusted regression analysis. Usual nutrient intake distributions, generated using the National Cancer Institute method, were used to determine the prevalence of nutrient inadequacy or the potential risk of excessive intakes from food sources alone and from the combination of food plus supplements. Of these Canadian children, 10 % were breakfast non-consumers, 33 % were consumers of RTEC breakfasts and 57 % were consumers of other types of breakfasts. Non-consumption of breakfast increased with age (4–8 years: 2 %; 9–13 years: 9 %; 14–18 years: 18 %). Breakfast consumers had higher covariate-adjusted intakes of energy, many nutrients and fibre, and lower fat intakes. The prevalence of nutrient inadequacy for vitamin D, Ca, Fe and Mg (from food alone or from the combination of food plus supplements) was highest in breakfast non-consumers, intermediate in consumers of other types of breakfasts and lowest in consumers of RTEC breakfast. For vitamin A, P and Zn, breakfast non-consumers had a higher prevalence of nutrient inadequacy than both breakfast groups. The potential risk of excessive nutrient intakes was low in all groups. Efforts to encourage and maintain breakfast consumption in children and adolescents are warranted.